Run to the board game: Its implementation in teaching English vocabulary - Sharifah, Ferly; Megawati, Fika; Novita, Dian; Astutik, Yuli (Journal of Research on English and Language Learning (J-REaLL), 2024)
In the era of globalization, mastering English is crucial for international communication. However, the success of English education in Indonesia is often hindered by limited language skills, particularly in vocabulary, which significantly affects students' comprehension. This challenge underscores the importance of fostering students' motivation to learn, as motivation serves as a key driver for academic success. This study employed a qualitative case study approach to investigate the implementation of the "Run to the Board" game as a method to teach English language skills at a junior high school. Participants were Kampus Mengajar batch 4 student teachers. Data collected through observations, interviews, and documentation were analyzed qualitatively. The findings of this study enrich the theoretical understanding of the "Run to the Board" (RTTB) method and offer practical insights for English language educators. This research provides alternative implementations of RTTB to suit diverse classroom contexts and explores the reflections of pre-service English teachers in applying this game. These reflections highlight the challenges and strategies involved in effectively utilizing RTTB, offering a valuable perspective for improving student engagement and vocabulary acquisition through innovative teaching methods. The results are expected to inspire teachers to be more creative in boosting students' self-confidence and addressing vocabulary challenges that impede their English proficiency.